PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP KEDISIPLINAN DAN KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN MERAUKE - Sopia Betaubun; Siti Haerani; Andi Reni (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the effect of empowerment and motivation to discipline and employee performance at the Department of Education and Culture of Merauke Regency. The type of this research is quantitative descriptive research that is the type of research that emphasizes the testing of theories through the measurement of research variables with numbers and requires data analysis with statistical procedures. The measurement tool of this research is a questionnaire, the data obtained in the form of answers from employees to the questions posed. The results of this study found that empowerment has a positive (0.672) and significant (0,000) effect on work discipline, positive (0.345) and significant (0,000) motivation to work discipline, empowerment has positive (1,139) and significant (0,000) impact on performance, (0,015) and not significant (0,756) to performance, discipline has negative effect (-0,224) and significant to performance 0,004.